Analisis Kepuasan Pengunjung Terhadap Terapan Visitor Management Di Kawasan Candi Prambanan Dengan Metode Importance Performance Analysis - Novi Irawati (STIE Pariwisata API Yogyakarta, 2019)
Prambanan Temple also known as Roro Jonggrang Temple is the biggest Hinduism temple in Indonesia. It was built in the 9th century AD. This tourism destination has become one of the most popular tourism destinations with high number visitor visits whether local or foreign. With its large site coverage, visitor management analyzes are needed as one of the most important factors to maximize the visitor number and to minimize the negative impact that can be occurred. The purpose of this research is to determine some indicators of visitor management that affects the visitor satisfaction valuation. The research method is by using importance performance analysis. The valuation result will become the basis of the Prambanan temple sustainable development plan in the future. So that, the satisfaction and memorable value of the visitor would be improved as well as the number of the visitor, and also it can educate the visitor about the heritage conservation value at the same time.